Development and Performance Evaluation of WO₃/ZnO Composite Membranes for Antibiotics Wastewater Treatment - Muhammad Itsar Hanif; Andri Cahyo Kumoro; Tutuk Djoko Kusworo (Waste Technology, 2026)
The contamination of water resources with pharmaceutical pollutants, particularly tetracycline (TC), has become a pressing environmental issue. This poses a significant threat to ecosystems and public health, as untreated wastewater can lead to the spread of antibiotic resistance. In this study, we explore the potential of PVDF-based membranes integrated with WO₃/ZnO composites for effectively removing TC and COD from wastewater. Membranes with varying concentrations of WO₃/ZnO (0.25%, 0.75%, 1.25%) were evaluated in terms of flux, pollutant rejection efficiency, and pore properties. Among the tested membranes, MV-3 (PVDF neat 13% + WO₃/ZnO 1.25%) demonstrated the best performance, achieving 98.28% rejection for TC and 87.72% for COD. Additionally, MV-3 exhibited the highest porosity (67.81%), although flux decreased moderately. This highlights the trade-off between high rejection efficiency and flux but demonstrates that the addition of WO₃/ZnO to PVDF membranes can provide a balanced solution for efficient wastewater treatment.